The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
SPE Annual Technical Conference and Exhibition 1981
DOI: 10.2118/10179-ms
|View full text |Cite
|
Sign up to set email alerts
|

Transient Pressure Analysis: Finite Conductivity Fracture Case Versus Damaged Fracture Case

Abstract: This work presents the basic pressure behavior differences between a finite conduc tivity fracture and different types of damaged fractures. Two kinds of fracture damage conditions are studied: a) a damaged zone around the fracture, and b) a damaged zone within the fracture in the vicinity of the wellbore. The first case is caused by the fracturing fluid loss in the formation and the last case 1S originated by crushing, embedding or loss of propant within the fracture in the vicin ity of the wellbore. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…A large number of studies have shown that when the vertical fractured well is in production state, it induces twodimensional elliptic seepage in the stratum and will form the conjugate isobaric elliptical equipotential line and hyperbola streamline group which uses the fractures endpoint as the main focus [20]. So it is more close to reality to use the elliptic coordinates to describe the vertical fractured well seepage physical process.…”
Section: Establishment Of the Mathematical Modelmentioning
confidence: 99%
“…A large number of studies have shown that when the vertical fractured well is in production state, it induces twodimensional elliptic seepage in the stratum and will form the conjugate isobaric elliptical equipotential line and hyperbola streamline group which uses the fractures endpoint as the main focus [20]. So it is more close to reality to use the elliptic coordinates to describe the vertical fractured well seepage physical process.…”
Section: Establishment Of the Mathematical Modelmentioning
confidence: 99%
“…The early work of Fetkovich (1980) and Cinco-Ley and Meng (1981) and the more recent work of Blasingame et al (1991) and Agarwal et al (1999) includes information on type-curve analyses. Modern RTA can provide a number of sophisticated graphical techniques to identify flow regimes and model production profiles.…”
Section: Rate Transient Analysis (Rta) In Unconventional Reservoirsmentioning
confidence: 99%
“…It is noted that Eq. A-10 is the definition for fracture face skin for a hydraulically fractured reservoir, as introduced by Cinco-Ley and Samaniego-V. (1981).…”
Section: ( ) Eq A-1mentioning
confidence: 99%